Schistosomiasis Mansoni: Novel Chemotherapy Using a Cysteine Protease Inhibitor - Maha‐Hamadien Abdulla; Kee‐Chong Lim; Mohammed Sajid; James H. McKerrow; Conor R. Caffrey (2007)
Schistosomiasis is a chronic, debilitating parasitic disease infecting more than 200 million people and is second only to malaria in terms of public health importance. Due to the lack of a vaccine, patient therapy is heavily reliant on chemotherapy with praziquantel as the World Health Organization-recommended drug, but concerns over drug resistance encourage the search for new drug leads.The efficacy of the vinyl sulfone cysteine protease inhibitor K11777 was tested in the murine model of schistosomiasis mansoni. Disease parameters measured were worm and egg burdens, and organ pathology including hepato- and splenomegaly, presence of parasite egg-induced granulomas in the liver, and levels of circulating alanine aminotransferase activity as a marker of hepatocellular function. K11777 (25 mg/kg twice daily [BID]), administered intraperitoneally at the time of parasite migration through the skin and lungs (days 1-14 postinfection [p.i.]), resulted in parasitologic cure (elimination of parasite eggs) in five of seven cases and a resolution of other disease parameters. K11777 (50 mg/kg BID), administered at the commencement of egg-laying by mature parasites (days 30-37 p.i.), reduced worm and egg burdens, and ameliorated organ pathology. Using protease class-specific substrates and active-site labeling, one molecular target of K11777 was identified as the gut-associated cathepsin B1 cysteine protease, although other cysteine protease targets are not excluded. In rodents, dogs, and primates, K11777 is nonmutagenic with satisfactory safety and pharmacokinetic profiles.The significant reduction in parasite burden and pathology by this vinyl sulfone cysteine protease inhibitor validates schistosome cysteine proteases as drug targets and offers the potential of a new direction for chemotherapy of human schistosomiasis.